Alfabetização científica nos anos iniciais: necessidades formativas e aprendizagens profissionais da docência no contexto dos sistemas de avaliação em larga escala - Pizarro, Mariana Vaitiekunas [UNESP] (2014)
The present research, inspired by the principles contained in the Harbermasian Theory of Communicative Action (TAC) reviewed the scientific literacy in primary school with an emphasis in teacher knowledge, professional teaching and learning of the possible training needs generated in the context of large scale assessment. The objective of this research was to identify and describe the professional learning and knowledge of teachers in the primary school to teaching science and to investigate possible training needs generated in the context of the large scale assessment for the promotion of scientific literacy and conditions of the interaction between teacher and researcher, with an emphasis on communication skills, could favor the construction of professional knowledge of teaching. Justified as considering the challenges faced by teachers in the primary school to comtemplate a teaching of science quality through its multifaceted practice years, which corresponds to the teaching of several specific areas and at the same time, it needs to adjust to the demands arising in the objective school environment from the deployment of large scale assessment and curricula tied to them. The study included a literature that presents dissertations, theses and published papers in repected journals in the field with the purpose of mapping studies that have addressed the indicators of scientific literacy and the impact of large scale assessments in science teaching. Collaborated with the research, a qualitative one, two teachers in the primary and public school in São Paulo, who participated in situations of dialogue with the researcher and were invited to talk about their practice in science, the curriculum proposed by the Education Department of the State for the primary school, the scientific literacy and its indicators, expectations regarding the effects that their practices generate the learning of their students and the changes experimented in the...